2023
DOI: 10.3390/quat6010013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Linkages between Ecosystem Services and Land Use/Land Cover Changes in Matenchose Watershed, Rift Valley Basin, Ethiopia

Abstract: The global ecosystem services that are essential to sustaining life on the planet have been disrupted by different anthropogenic activities. This study’s objective is to examine how ecosystem services vary with changes in land use and land cover (LULC) across 29 years at the Matenchose watershed. Landsat images for 1991 (TM), 2003 (ETM+), and 2020 (OLI-8) were used for the categorization of LULC. To evaluate the changes in ecosystems service valuations (ESVs) as a result of LULC changes in combination with Arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Land-use change is a key factor influencing ecosystem services [25]. Land-use change reflects the complex interactions between climate change and human activities and is closely linked to several terrestrial processes such as biodiversity, surface energy balance, atmospheric circulation, and carbon cycling [26,27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Land-use change is a key factor influencing ecosystem services [25]. Land-use change reflects the complex interactions between climate change and human activities and is closely linked to several terrestrial processes such as biodiversity, surface energy balance, atmospheric circulation, and carbon cycling [26,27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lower results reported by various scholars, for instance, Mathewos et al [ 6 ] at Matenchose watershed reported 21 t/ha/y; Kouli et al [ 106 ] reported 10 t/ha / y; Haregeweyn et al [ 107 ] described 29.9 t/ha/y in southern Ethiopia; Gerawork and Moges [ 108 ] explored 7.47 t/ha/y; Bekele and Gemi [ 109 ] reported 2.2 t/ha/y. The variety in the outcomes might be credited to the fluctuating soil factors in the different review regions.…”
Section: Resultsmentioning
confidence: 73%
“…In this research, RUSLE together with Arc GIS was used to estimate the soil loss [ 7 ]. This model is widely applied throughout the world where data sources are scarce [ 6 , 7 , 26 , 52 ]. The soil loss estimation using RUSLE in arc GIS approaches embroils the amalgamation of five various inputs (R, K, LS, C, and P) as shown in equation (1) below [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation